An exploration of constructions of masculinity : a narrative study of young Zulu men's stories of 'being a man' - Maxwell, Justin Kennedy (Rhodes University, Faculty of Humanities, Department of Psychology, 2005)
Previously understood as a fixed and universal set of behaviours social constructionists are now arguing that masculinity is contextual and fluid, reflecting a multiplicity of different understandings. Within any 'cultural environment' the discourse of masculinity, culturally and historically bound, expresses attitudes and behaviours that shape the understanding of what it means to be a man. Adopting a narrative approach and analysis this research explores the stories of six Zulu men in seeking to elicit the aspects of their masculinity and show how these men negotiate an identity 'position' from the social narratives available to them. It was found that while the ideal Adult (responsible) man contrasts with the Young man's ('isoka' ) position there is a consistently hegemonic and patriarchal notion of masculinity.
Keywords: Masculinity -- South Africa -- KwaZulu-Natal; Men -- South Africa -- Psychology; Discourse analysis, Narrative -- Psychological aspects; Zulu (African people) -- Social life and customs; Men -- South Africa -- KwaZulu-Natal